Staging Shakespeare. Renato Sarti’s “rude mechanicals” (tragic) comedy (Altre Modernità, 2017)
"The same person," according to Socrates, "should know how to write comedy and tragedy; anybody who excels at tragedy will also be a master of comedy." Shakespeare's work, seeing its many registers and styles, seems to fully confirm Socrates' statement. But too often, on the most important stages in Italy, the tragic dimension of Shakespeare's plays prevails, and the actors seem to orient their actorial style in that direction. Yet with the Bard you can laugh, in actual fact you must laugh. Renato Sarti, director of Milan's "Teatro della Cooperativa" (Cooperativa Theatre), artistic director and playwright, seems to embody, through his own theatrical productions, the versatility of genre Socrates advocated.